The self esteem and cyberbullying behaviour of islamic students on social media - Ningsih, Wirda (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2024)
Purpose - This research investigates the correlation between self-esteem and cyberbullying behavior among Islamic higher education students on social media platforms, addressing a critical gap in understanding these behaviors within a specific cultural and religious context. Method - Employing a descriptive-correlational quantitative survey design, the study involved 321 participants. Data analysis was conducted using Pearson correlation to explore the relationship between self-esteem and cyberbullying behaviors among students in Islamic higher education institutions. Results - The analysis revealed a strong and significant relationship between self-esteem and cyberbullying behaviors in this population, emphasizing the interplay between psychological factors and online behaviors in a distinct cultural setting. Implication - This study offers crucial insights into cyberbullying within a unique cultural and religious framework, paving the way for targeted interventions, informed policymaking, and further academic inquiry into the dynamics of cyberbullying in similar contexts. Originality/Value - As the first research to focus specifically on the cyberbullying behavior of Islamic students on social media, this study contributes a novel perspective to the broader cyberbullying literature and highlights the importance of cultural sensitivity in understanding and addressing online behaviors *** Tujuan - Penelitian ini menyelidiki korelasi antara harga diri dan perilaku cyberbullying di kalangan mahasiswa pendidikan tinggi Islam di platform media sosial, untuk mengatasi kesenjangan kritis dalam memahami perilaku ini dalam konteks budaya dan agama tertentu. Metode - Menggunakan desain survei kuantitatif deskriptif-korelasional, penelitian ini melibatkan 321 peserta. Analisis data dilakukan dengan menggunakan korelasi Pearson untuk mengeksplorasi hubungan antara harga diri dan perilaku cyberbullying di kalangan mahasiswa di lembaga pendidikan tinggi Islam. Hasil - Analisis mengungkapkan hubungan yang kuat dan signifikan antara harga diri dan perilaku cyberbullying dalam populasi ini, yang menekankan interaksi antara faktor psikologis dan perilaku online dalam lingkungan budaya yang berbeda. Implikasi - Studi ini menawarkan wawasan penting tentang cyberbullying dalam kerangka budaya dan agama yang unik, membuka jalan bagi intervensi yang ditargetkan, pembuatan kebijakan yang terinformasi, dan penyelidikan akademis lebih lanjut tentang dinamika cyberbullying dalam konteks yang sama. Keaslian/Nilai - Sebagai penelitian pertama yang secara khusus berfokus pada perilaku cyberbullying siswa Islam di media sosial, penelitian ini memberikan kontribusi perspektif baru pada literatur cyberbullying yang lebih luas dan menyoroti pentingnya kepekaan budaya dalam memahami dan menangani perilaku online